Dakwah dan Toleransi Umat Beragama (Dakwah Berbasis Rahmatan Lil Alamin) - Muhammad Rifat (Alhadharah: Jurnal Ilmu Dakwah, 2017)
Dakwah activity based on enlightenment of the people, must necessarily require a comprehensive understanding of the religious tolerance. Tolerance which etymologically means patience, showing tolerance or patience should be reflected in the implementation of dakwah activities. Religious tolerance is very important when viewed from the condition of the nation and the State with a multi-ethnic, cultural, and religious social life. Therefore, through the mass media and dakwah-oriented religious action should not just be limited to the delivery of the message of Islam, but it must be coupled with a sense tolerant of different views and beliefs